Sosialisasi Pengelolaan Sampah Melalui Papan Edukasi Sampah Dan Ecobrick Di Desa Kubang Utara Sikabu, Sawahlunto: Upaya Melawan Kebiasaan Buruk Membuang Sampah Sembarangan Dan Meningkatkan Kesadaran Masyarakat Terhadap Energi Dan Daur Ulang Sampah - Sandra Dewi; Alsil Nofita; Lyoni Selfira; Wafda Aulia idris; Yessyca Sianturi; Yuri Ariani (CV. ITTC INDONESIA, 2025)
As one of the most populous countries in the world, Indonesia is facing serious challenges in waste management, particularly in rural areas that have not yet developed adequate waste treatment systems. Kubang Utara Sikabu Village in Sawahlunto City serves as an example of such a region, where structured and sustainable waste management practices are still lacking. This community service project aimed to enhance residents’ understanding of proper waste management through an educational and participatory approach. The research employed a qualitative descriptive method, with data collected through field observation, interviews with local residents, documentation of activities, and a community outreach program conducted on July 3, 2025. The outreach covered topics such as types of waste, the environmental hazards of inorganic waste, the application of the 3R principles (Reduce, Reuse, Recycle), ecobrick-making practices, and the installation of educational boards displaying information on the decomposition times of various waste materials. The results indicated an increase in public awareness regarding waste sorting and processing. Community responses were largely positive, particularly concerning plastic pollution and the benefits of recycling activities. This initiative also integrated science education elements, including the study of material properties, energy concepts, and the application of science in everyday life. Overall, this outreach program marked a significant first step toward fostering a culture of responsible and sustainable waste management at the village level.